Applied longitudinal data analysis for epidemiology : a practical guide - Twisk, Jos W. R., 1962- (Cambridge University Press, 2003)
In this book the most important techniques available for longitudinal data analysis are discussed, including simple techniques such as the paired t-test and summary statistics, and more sophisticated techniques such as generalised estimating equations and random coefficient analysis. This practical guide is suitable for non-statisticians involved in medical research and epidemiology.